(untitled) (Italian Review of Legal History, 2015)
In Lombardy during the Restoration era the legal science tends to concentrate on the codes’ content and to be influenced by the French one. This inclination is even stronger in the field of commercial law as the Austrians had decided not to abrogate the Code de commerce in the Kingdom of Lombardy-Venetia. Against this background, it is remarkable that in 1842 the Istituto Lombardo chooses a theme for its “premio scientifico biennale” that spurs the competitors to deal with company law with a critical approach. Among the submitted entries, Francesco Restelli’s one is the most interesting: he drew up a veritable alternative to title III, book I of the Commercial Code.